An implementation of blockchain technology in sustainable apparel supply chain - Kalithazan, Kausalyah; Fazeeda, Mohamad; Zainul Abideen, Ahmed (Penerbit Universiti Malaysia Pahang, 2024)
The improper management of supply chain may lead to the occurance of numerous complications within a company, such as financial loss in inventory and distribution. It is imperative to inform businesses, including those in the apparel industry, on how to improve their supply chain using advanced technologies like blockchain technology. Therefore, the purpose of this study was to determine the challenges of sustainable apparel in supply chain and to improve apparel supply chain by implementing the blockchain technology. Qualitative research design was employed and the data was collected via a face-to-face interview. The respondent acknowledged the company’s inadequate supply chain management for sustainable apparel. Such findings add to the body of knowledge on blockchain technology and sustainable supply chains by demonstrating how blockchain technology can change and benefit the apparel industry as well as improve the interaction between suppliers and consumers.